Genomic and epidemiological characterisation of a dengue virus outbreak among blood donors in Brazil. Issue 1 (December 2017) - Faria, Nuno; Costa, Antonio; Lourenço, José; Loureiro, Paula; Lopes, Maria; Ribeiro, Roberto; Alencar, Cecilia; Kraemer, Moritz; Villabona-Arenas, Christian; Wu, Chieh-Hsi; Thézé, Julien; Khan, Kamran; et al.
Abstract Outbreaks caused by Dengue, Zika and Chikungunya viruses can spread rapidly in immunologically naïve populations. By analysing 92 newly generated viral genome sequences from blood donors and recipients, we assess the dynamics of dengue virus serotype 4 during the 2012 outbreak in Rio de Janeiro. Phylogenetic analysis indicates that the outbreak was caused by genotype II, although two isolates of genotype I were also detected for the first time in Rio de Janeiro. Evolutionary analysis and modelling estimates are congruent, indicating a reproduction number above 1 between January and June, and at least two thirds of infections being unnoticed. Modelling analysis suggests that viral transmission started in early January, which is consistent with multiple introductions, most likely from the northern states of Brazil, and with an increase in within-country air travel to Rio de Janeiro. The combination of genetic and epidemiological data from blood donor banks may be useful to anticipate epidemic spread of arboviruses.